Consultation-Liaison Psychiatry in Tertiary Level Hospital In Nepal - Ranjan, Sanjeev; Poudel, R; Pandey, P (Health Renaissance, 2016)
Background: Consultation-liaison (C-L) psychiatry has emerged as a separate specialty in psychiatry in developed countries. It is an important component of a multidisciplinary hospital. In developing countries, this specialty is being underused and less emphasized. The reason for this could also be due to scarcity of study in this field in developing countries. Objective: To assess the socio-demographic and clinical variables of patients referred for C-L psychiatry in a tertiary hospital in western region of Nepal. Methods: One hundred consecutive inpatients referred for C-L psychiatry were assessed for socio demographic referrals, reason for referral and their attitude towards psychiatric referral. Each patient was evaluated in detail by consultant psychiatrists and the psychiatric diagnosis made according to the International Classification of Disease-10 (ICD-10) criteria. Results: The mean age of the sample was 40.28 years (±18.76) with male to female ratio of 1.27:1. The department of internal medicine was the most referring department (56%) and majority of the patients referred had positive attitude towards psychiatric referral (94%). Alcohol dependence syndrome (ADS) and intentional self harm (21% each) were the most common psychiatric diagnoses made. Conclusions: psychiatry consultation was done mostly by the department of internal medicine and majority of patient had positive attitude toward psychiatric referral. Health Renaissance 2014;12(3): 170-174